Bridging the Gap: A Literature Review on the Integration of Accounting Information Systems (AIS) into Mainstream Accounting Research - Santa Kristina Sese; Farah Qollbia (International Journal of Management, Accounting & Finance (KBIJMAF), 2025)
This qualitative literature review explores the integration of Accounting Information Systems (AIS) into mainstream accounting research. The study identifies significant barriers, including limited representation of AIS topics in mainstream journals and divergent research methodologies. Despite these challenges, the review highlights the growing importance of digitalization and emerging technologies, which present opportunities for AIS to significantly impact accounting practices. The findings suggest that fostering interdisciplinary collaboration, embracing methodological diversity, and developing a unified research agenda are essential steps toward achieving greater integration. This integration is crucial for harnessing the full potential of AIS research to drive innovation and address complex challenges in the digital age. The review also acknowledges limitations, such as the selection of articles and linguistic constraints, which may impact the generalizability of the findings.